Health economic evaluation of moist wound care in chronic cutaneous leishmaniasis ulcers in Afghanistan - Stahl, Hans-Christian; Dong, Hengjin; Sauerborn, Rainer (Infectious diseases of poverty, 2018)
Background: The present health economic evaluation in Afghanistan aims to support public health decision makers and health care managers to allocate resources efficiently to appropriate treatments for cutaneous leishmaniasis (CL) elicited by Leishmania tropica or Leishmania major. Methods: A decision tree was used to analyse the cost and the effectiveness of two wound care regimens versus intra-lesional antimony in CL patients in Afghanistan. Costs were collected from a societal perspective. Effectiveness was measured in wound free days. The incremental cost-effectiveness ratio (ICER) and incremental net monetary benefit (NMB) were calculated. The model was parameterized with baseline parameters, sensitivity ranges, and parameter distributions. Finally, the model was simulated and results were evaluated with deterministic and probability sensitivity analyses. Final outcomes were the efficiency of the regimens and a budget impact analysis in the context of Afghanistan. Results: Average costs per patients were US$ 11 (SE = 0.016) (Group I: Intra-dermal Sodium Stibogluconate [IL SSG]), US$ 16 (SE = 7.58) (Group II: Electro-thermo-debridement [ETD] + Moist wound treatment [MWT]) and US$ 25 (SE = 0.48) (Group III: MWT) in patients with a single chronic CL ulcer. From a societal perspective the budget impact analysis shows that the regimens’ drug costs are lower than indirect disease cost. Average effectiveness in wound free days are 177 (SE = 0.36) in Group II, 147 (SE = 0.33) in Group III, and 129 (SE = 0.27) in Group I. The ICER of Group II versus Group I was US$ 0.09 and Group III versus Group I US$ 0.77, which is very cost-effective with a willingness-to-pay threshold of US$ 2 per wound free day. Within a Monte-Carlo probabilistic sensitivity analysis Group II was cost-effective in 80% of the cases starting at a willingness-to-pay of 80 cent per wound free day. Conclusions: Group II provided the most cost-effective treatment. The non-treatment alternative is not an option in the management of chronic CL ulcers. MWT of Group III should at least be practiced. The cost-effectiveness of Group III depends on the number of dressings necessary until complete wound closure.